SCIENTIFIC JUSTIFICATION OF MEASURES TO ENSURE SAFE WORKING CONDITIONS FOR EMPLOYEES ENGAGED IN MODERN ALUMINUM PROFILE PRODUCTION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Based on the conducted research, a set of preventive measures has been developed to optimize working conditions and preserve the health of workers engaged in modern aluminum profile production.